Reuse of oak chips for modification of the volatile fraction of alcoholic beverages - Coelho, Eduardo João Louro (2021)
New or used barrels can be applied in ageing of alcoholic beverages. Compounds adsorbed in wood migrate between beverages along with wood extractives. As barrel ageing is costly and time-consuming, processes using wood fragments have been gaining interest. These generate wood residues for which the reuse is still not well established. This work aims at the reuse of oak fragments for the additive ageing of alcoholic beverages. Oak chips, previously immersed in fortified wine, were applied to beer, wine and grape marc spirit. Wood compounds and adsorbed wine volatiles were extracted, with more impact and satisfactory yields on beer composition. Also, wood adsorbed beverages compounds in a subtractive ageing phenomena. Beer formulations using different binomial wood concentration/temperature combinations were generated and presented to trained tasters. Higher temperatures and wood concentrations led to prominence of wood descriptors and lower perception of fruity and floral aromas, reflecting the changes in chemical composition.